PENGARUH MOTIVASI DAN ETIKA KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA PT BANK MALUKU MALUT - Aulia Rahim, Ode (Journal of Innovation Research and Knowledge, 2025)
This study reviews the effect of motivation and work ethics on employee performance with job satisfaction as a mediating variable at PT Bank Maluku Malut. The population in this study were employees of PT Bank Central Asia Kediri Branch, with a total sample of 111 respondents. The sampling techniqueuses the saturation sampling method using PLS-SEM analysis. The results show that motivation has a significant effect on employee performance at PT Bank Maluku Malut, work ethics has a significant effect on employee performance at PT Bank Maluku Malut, motivation has a significant effect on job satisfaction at PT Bank Central Asia Kediri Branch, work ethics has a significant effect significant effect on job satisfaction at PT Bank Maluku Malut, job satisfaction has a significant effect on employee performance at PT Bank Maluku Malut, motivation has a significant effect on employee performance through job satisfaction at PT Bank Maluku Malut, and work ethics has no effect significantly to employee performance through satisfaction at PT Bank Maluku Malut